2011
DOI: 10.1002/pi.3084
|View full text |Cite
|
Sign up to set email alerts
|

Two‐step synthesis and properties of a magnetic‐field‐sensitive modified maltodextrin‐based hydrogel

Abstract: A magnetic-field-sensitive modified maltodextrin-based hydrogel (ferrogel) was synthesized. Fourier transform infrared and 13 C-CP/MAS NMR spectral analyses confirmed the efficiency of the gelling process. X-ray diffraction analysis revealed the appearance of new crystalline planes in the hydrogel diffractograms after embedding of magnetite nanoparticles. Magnetization curves and Mössbauer analysis revealed that the magnetic hydrogel has a high lattice strain due to bonded iron atom covalence. Moreover, some m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
21
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 25 publications
(34 reference statements)
2
21
0
Order By: Relevance
“…103 Other widely applied methods for remediation of water and industrial wastewater polluted with dyes include ion exchange, 104 Unlike the solid adsorbents, the polysaccharide-based hydrogels appear as excellent tool for the removal of aqueous solutes, including dyes and pigments, 103,113 Among various types of polysaccharide hydrogels, those ones based on chitin-and chitin-derivatives are promising adsorbents for the adsorption, removal and separation of anionic and cationic dyes from aqueous solutions. 94 Chitin and its derivatives may be converted into hydrogels and applied as excellent adsorbent materials for adsorption, removal and separation of different pollutant dyes from water and industrial wastewater. 114 However, the adsorption efficiency mainly depends on the type of applied hydrogel.…”
Section: As Adsorbent Of Dyes From Wastewater Resulting From Industrimentioning
confidence: 99%
See 1 more Smart Citation
“…103 Other widely applied methods for remediation of water and industrial wastewater polluted with dyes include ion exchange, 104 Unlike the solid adsorbents, the polysaccharide-based hydrogels appear as excellent tool for the removal of aqueous solutes, including dyes and pigments, 103,113 Among various types of polysaccharide hydrogels, those ones based on chitin-and chitin-derivatives are promising adsorbents for the adsorption, removal and separation of anionic and cationic dyes from aqueous solutions. 94 Chitin and its derivatives may be converted into hydrogels and applied as excellent adsorbent materials for adsorption, removal and separation of different pollutant dyes from water and industrial wastewater. 114 However, the adsorption efficiency mainly depends on the type of applied hydrogel.…”
Section: As Adsorbent Of Dyes From Wastewater Resulting From Industrimentioning
confidence: 99%
“…92,93 For instance, Cs-based magnetic hydrogels were used to remove textile dyes from industrial effluents 92 and adsorption of lead, cadmium and cupper from aqueous solutions. 94 Magnetic hydrogel based on polyacrylamidegrafted Cs was applied as an efficient adsorbent for the removal of copper, lead, and mercury ions from aqueous solutions in respective single, binary, and ternary metal mixtures. 88 It has been reported that the addition of different components in a hydrogel network improves their adsorption capacity 95 since such included compounds may function as dispersing agents to increase the interconnected porous structure of polymer hydrogels.…”
mentioning
confidence: 99%
“…Thus, a greater amount of magnetite increases the degree of crosslinking, as iron ions form covalent bonds with the hydrogel network and thereby hinder the diffusion of water or metal through the hydrogel. Upon contact with water, electrostatic repulsion forces among polymer segments in the hydrogel decrease due to the presence of iron ions, leading to a reduction in both the water uptake and metal [25,28,29]. Concluding, it may be said that the magnetite nanoparticle in the hydrogel network affected both the diffusion process and the interaction of Cd 2+ with the active sites.…”
Section: Non-linear Isotherm Models Of Langmuir Freundlich and Redlimentioning
confidence: 86%
“…Due to this, it was noted that the degree of swelling for hydrogels with no magnetite nanoparticles were higher than for hydrogels with magnetite nanoparticles. The highest degree of swelling of the CS-based hydrogel relative to hydrogels based on M-malto and M-GA may be due to the differences in the degree of crosslinking noted during the characterizations [25,28,29].…”
Section: Swelling Kinetics In Watermentioning
confidence: 90%
See 1 more Smart Citation